Oligoclonal and monoclonal bands after single autologous stem cell transplant in patients with multiple myeloma: impact on overall survival and progression-free survival. Issue 10 (October 2014) - Jimenez-Zepeda, Victor H.; Reece, Donna E.; Trudel, Suzanne; Franke, Norman; Winter, Andrew; Chen, Christine; Tiedemann, Rodger; Kukreti, Vishal
Abstract Recently, the occurrence of oligoclonal and monoclonal bands (OB/MB) unrelated to the original clone has been reported in patients with multiple myeloma who undergo autologous stem cell transplant (ASCT) and/or receive treatment with novel agents. The aim of our study was to assess the impact of OB/MB occurrence on overall (OS) and progression-free survival (PFS) for patients with MM undergoing single ASCT at our institution. All consecutive patients with documented MM undergoing single ASCT from January 2000 to December 2012 were evaluated. Ninety-nine patients (11.8%) developed OB/MB at day 100 post-ASCT (32.3%, OB and 67.7%, MB). Multivariate analysis identified the development of OBs/MBs as an independent favorable prognostic factor for OS and PFS (p = 0.008 and 0.012, respectively). In conclusion, the occurrence of OB/MB is an important prognostic factor in patients with MM who undergo ASCT. Its impact on clinical outcomes should be prospectively validated and its biological significance further elucidated.